The future development of world records - Franziska K. Kruse; Wolfgang Maennig (University of Hamburg, Faculty of Business, Economics and Social Sciences, Chair for Economic Policy, 2017)
We conduct an innovative analysis of sporting world records by a) using economic instead of sporting determinants and b) by using multivariate stochastic frontier functions. Using data from 48 different disciplines between 1970 and 2014, we show that world records are close to full efficiency and therefore actual athletic frontiers. Forecasts including economic determinants imply that the dynamics of world records largely depend on the dynamics of the frontiers and their driving forces, i.e., socio-economic developments.
Keywords: C10; C23; C53; L83; 330; World records; productivity growth; stochastic frontier function; technical efficiency